Corporate reporting provides insight into companies' commitment to gender equality - Anja Kirsch; Virginia Sondergeld; Philipp Alexander Thompson; Katharina Wrohlich (DIW Weekly Report, 2023)
Many companies in Germany must provide information beyond financial figures in their annual reports. For some years now, legislators have increasingly required information on non-financial aspects, such as the shares of women in leadership positions. Using a quantitative text analysis of annual reports, this second report in the 2023 DIW Berlin Women Executives Barometer shows that the major publicly listed corporations in Germany implement the reporting requirements very differently. Reporting about women and leadership positions increased overall between 2009 and 2020 in line with the requirements. However, there were clear differences in the companies' focus: There is an equality-oriented group of companies that reports extensively about concrete measures to increase the share of women in leadership positions. This group has significantly more women on their supervisory boards than the other group, compliance-oriented companies, which seem to be mainly concerned with fulfilling the legal requirements. Companies' reporting on women and leadership positions is thus an indicator and useful signal to outside stakeholders of how serious companies are about gender equality.
Keywords: D22; J78; K38; M12; M14; M51; 330; accountability; board composition; board diversity; boards of directors; CEOs; corporate boards; corporate governance; CSR; diversity; executive boards; female directors; gender equality; gender quota; Germany; leadership positions; managers; non-financial disclosure; non-financial reporting; private companies; public companies; supervisory boards